2018
DOI: 10.3389/fgene.2018.00594
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diagnostic Evaluation of Trio-Based Whole Exome Sequencing Among Children With Diagnosed or Suspected Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a group of clinically and genetically heterogeneous neurodevelopmental disorders. Recent tremendous advances in the whole exome sequencing (WES) enable rapid identification of variants associated with ASD including single nucleotide variations (SNVs) and indels. To further explore genetic etiology of ASD in Chinese children with negative findings of copy number variants (CNVs), we applied WES in 80 simplex families with a single affected offspring with ASD or suspected ASD, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 52 publications
4
34
1
Order By: Relevance
“…Individual data points are superimposed onto means ± SEM. n = 15 +/+ males, 14 +/+ females, 8 +/− males (5 m+/p−, 3 m−/p+), and 12 +/− females (10 m+/p−, 2 m−/p+) social novelty [Katayama et al, 2016;Platt et al, 2017], whereas other groups reported no changes in this phase of the three-chamber test [Gompers et al, 2017;Jung et al, 2018]. Our Chd8 mutant mice perform statistically the same as wild-type in both the sociability (Figure 2 .…”
Section: Generation Of Chd8 +/E31t Micementioning
confidence: 91%
See 3 more Smart Citations
“…Individual data points are superimposed onto means ± SEM. n = 15 +/+ males, 14 +/+ females, 8 +/− males (5 m+/p−, 3 m−/p+), and 12 +/− females (10 m+/p−, 2 m−/p+) social novelty [Katayama et al, 2016;Platt et al, 2017], whereas other groups reported no changes in this phase of the three-chamber test [Gompers et al, 2017;Jung et al, 2018]. Our Chd8 mutant mice perform statistically the same as wild-type in both the sociability (Figure 2 .…”
Section: Generation Of Chd8 +/E31t Micementioning
confidence: 91%
“…A commonly used assay to test for social deficits in mice is the three-chamber test for sociability and social novelty [Crawley, 2004]. Previous characterizations of Chd8 mutant mice revealed no deficits in sociability on this assay [Gompers et al, 2017;Jung et al, 2018;Katayama et al, 2016;Platt et al, 2017;Suetterlin et al, 2018]. Some groups reported a deficit in recognizing Figure 1.…”
Section: Generation Of Chd8 +/E31t Micementioning
confidence: 93%
See 2 more Smart Citations
“…To date, over 50 cases have been reported in the literature (Dentici et al, ; Du et al, ; Fromer et al, ; Fukai et al, ; Gilissen et al, ; Gulsuner et al, ; Hashimoto et al, ; Homsy et al, ; Iossifov et al, ; Longoni et al, ; Matsumura et al, ; Neale et al, ; Stessman et al, ; White et al, ; Yavarna et al, ; Ye et al, ). Here we report insights from an allelic series of 21 distinct POGZ variants in 22 individuals with WHSUS.…”
Section: Introductionmentioning
confidence: 99%